Tourism in the Caribbean : competitiveness, upgrading, linkages and the role of public private partnerships (PPP) and public policy (ECLAC [Port of Spain]TT, 2007)
Explores and analyzes the contributions that public-private partnerships and public policy have made in the development of tourism in the Caribbean as tools for enhancing competitiveness in the Caribbean tourism industry. Analyzes also, the potential roles that they will continue to play in the future, especially in the process of building linkages between the tourism sector and the other sectors in order to increase net benefits from tourism to the region.
Bibliography: p. 58-59